Pengaruh Kegiatan Lempar Tangkap Bola Terhadap Motorik Kasar Anak Pada Usia 5-6 Tahun di Paud Anugerah GKPI Pearaja Tarutung - Elsa Konika Panjaitan; Rotua Samosir; Hisardo Sitorus (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The aim of this research was to determine the effect of ball throwing and catching activities on the gross motor skills of children aged 5-6 years at PAUD Anugerah GKPI Pearaja Tarutung. The method used in this research is a quantitative research method with a pre-experimental type of research in the form of "One Shot Case Study". The population is all group B students (aged 5-6 years) at PAUD Anugerah GKPI Pearaja Tarutung for the 2023/2024 academic year, totaling 40 people and this research is population research. Data was collected using an observation instrument of 15 items. The results of data analysis show that there is an influence of throwing and catching balls on the gross motor skills of children aged 5-6 years at PAUD Anugerah GKPI Pearaja Tarutung: 1) Test the analysis requirements: a) positive relationship test obtained by the value rxy = 0.556 > rtable(a=0.05,n=40) = 0.312, thus it is known that there is a positive relationship between variable X and variable Y. b) Testing a significant relationship obtained a value of tcount= 4.126 > ttable(a=0.05,dk=n-2=38)= 2.021, thus there is a significant relationship between variable X and variable Y. c) Test the regression coefficient of determination (r2) = 30.9%.2) Influence test: Regression equation test, obtained the regression equation Y ̂="14.87"+0.54X. Thus Ha is accepted and H0 is rejected.